ULTRA: A Digital Gamification Approach to Boosting Mathematical Creative Thinking and Self-Regulated Learning - Nopitasari, Dian; Kusumah, Yaya Sukjaya; Juandi, Dadang; Priatna, Bambang Avip (FKIP Universitas Lampung, 2025)
The Mathematics Education Game is a gamification-based teaching material specifically designed to develop mathematical creative thinking skills and self-regulated learningin high school students. This game adopts a Snakes and Ladders format, consisting of three learning modules covering core trigonometry: basic concepts, quadrants, special angles, trigonometric equations, trigonometric identities, double-angle identities, sums and differences of angles, and multiplication of trigonometric functions. The game developed in this study, Attractive Trigonometric Snakes and Ladders (ULTRA), aims to serve as an engaging digital learning resource for students in grades XI and XII. The purpose of this study is to examine the improvement in creative thinking skills and self-regulated learning of students who use ULTRA. The research method uses the ADDIE model and is evaluated through three research instruments: (1) a mathematical creative thinking test containing four essay questions to measure fluency, flexibility, originality, and elaboration; (2) a 24-item self-regulated learning questionnaire that assesses goal setting, monitoring, strategy use, and reflection; and (3) a 15-item student response questionnaire to assess usability and engagement. Effectiveness was analyzed using normalized gain, while validity and practicality were reviewed through expert assessment and descriptive data. The research subjects were 496 students from 16 classes, comprising 247 in the experimental class and 249 in the control class. This study concluded that ULTRA is valid, practical, and has potential as a digital medium for mathematics learning. Effectiveness testing conducted in four schools showed a moderate increase in N-Gain in mathematical creative thinking skills, as well as positive behavioral indicators of learning independence, indicating that ULTRA strengthens students' higher-order thinking skills and independence. Overall, the findings indicate that the ULTRA game has the potential to improve mathematical creative thinking and self-regulated learningwhile providing an engaging digital learning experience for students. Keywords: education game, creative thinking, self-regulated learning.